Identification and Classification of Risks in Trade - G. P. Fomin (Plekhanov Russian University of Economics, 2019)
The content of the majority economic objectives comes to optimum use of resources of different types, at the same time among various resources, such as natural, finance, etc., human capital tends to take the leading position as the most valuable one. Trade operations are not always conducted smoothly, sometimes errors can be observed, deviations from the set mechanism of economic process development can take place due to some reasons and because of those undesirable effects, damages can turn up, which in their turn can cause subsequent adverse phenomena. All of them are interconnected and interdependent. In order to prevent such situations it is necessary to identify risks to foresee possible development in the future. The article provides specificity of the algorithm for researching risks at trade enterprises and shows features of identification and complexity of classification schemes of factors and risks connected with damages. Trade activity is characterized by indicators, i.e. indices of economic activity, which should be controlled at all stages of trade and economic process implementation. Different versions of risk classification are proposed, which can be suitable for the next research in the field of trade.